From affectivity to subjectivity : Husserl's phenomenology revisited - Lotz, Christian (Palgrave Macmillan, 2007)
Shows that Husserl's Phenomenology and its key concept, subjectivity, is based on a concrete anthropological structure, such as self-affection and the bodily experience of the other.